Establishing Validity And Reliability of Semi-Structured Interview Questionnaire in Developing Risk Communication Module: A Pilot Study - Khin Thandar Aung; Rafiza Abdul Razak; Nor Nazrina Mohamad Nazry (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Needs analysis is a technique in collecting and accessing information relevant to course design. In the needs analysis, the interview is one of the methods and it involves asking in-depth questions using a structured or semi-structured guide to better understand the individual’s points of view. A pilot test for an interview is an important and useful process in conducting qualitative research. Its findings might indicate that some improvements for the major study are needed. This article will explore the advantages of the pilot study, how it was undertaken and the experiences and findings throughout the study. The pilot test was conducted by interviewing two nursing lecturers using Google Meet. This pilot test was conducted with three stages of an interview process such as a pre-interview, peri-interview and post-interview. There were no serious modifications were needed after data analysis of the pilot study was done. It indicates that the research instruments, semi-structured questions can be considered as valid and reliable and can be used for the real study. At the same time, the researcher recognized that the MOOC course and communication at risk module need details explanation because they are new for the participants and to make clear distinction between risk communication and therapeutic communication. This study gives the researchers valuable experiences in applying the three stages of the interview session. The most important, the findings of this study can be applied in the real study